Pre-CRRT furosemide and mortality in sepsis-associated AKI: A retrospective cohort study - Si-Ye Shen; Lu Fu; Dai-Yun Liang; Shao-Kang Wang; Hu Chen; Li-Jun Cao; Wei-Li Yu; Yun Sun; Zhong-Hua Lu (PLoS ONE, 2026)
Objective We aimed to assess whether pre-CRRT furosemide use in SAKI patients requiring CRRT is associated with 28-day mortality, and to evaluate its relationship with secondary outcomes including short-term mortality, in-hospital death, and length of stay. We also examined potential effect modification by CKD status and furosemide dosage. Design Retrospective cohort study. Setting Data were extracted from the MIMIC-IV database, a large publicly available critical care database. Participants A total of 969 adult patients with SAKI requiring CRRT were included. Intervention Patients were stratified based on pre-CRRT furosemide use (defined as administration within 72 hours prior to CRRT initiation). Propensity score matching (1:1) was applied to generate balanced cohorts (n = 560). Measurements Primary outcome: 28-day all-cause mortality. Secondary outcomes: 7-day mortality, 90-day mortality, in-hospital mortality, and length of ICU and hospital stay. Multivariable Cox regression was used to adjust for potential confounders. Results In the matched analysis, furosemide use was associated with significantly lower 28-day mortality (44.3% vs 58.6%; HR 0.58, 95% CI 0.46–0.73, p < 0.001). Consistent reductions were observed in 7-day mortality (HR 0.45), 90-day mortality (HR 0.59), and in-hospital mortality (HR 0.50; all p < 0.01). Subgroup analyses showed greater benefit in non-chronic kidney disease patients (interaction p = 0.021) and with high-dose furosemide (>90mg/72h; HR 0.62, 95% CI 0.45–0.85). Sensitivity analyses in the full cohort confirmed robustness (HR 0.59, 95% CI 0.49–0.72). The use of furosemide is related to the prolongation of CRRT startup time (1.52 vs 1.46 days). However, furosemide use was associated with prolonged median ICU stay (9.3 vs 6.1 days) and hospital stay (20.8 vs 12.5 days). Conclusions These findings suggest that, in this selected cohort, pre-CRRT furosemide use was associated with lower mortality and does not appear to be associated with harm from delayed CRRT initiation. However, due to the observational design, these results should be warrant confirmation in prospective, randomized controlled trials.